Modified silica aerogel, polyvinyl chloride composition, modified polyvinyl chloride plate, and refrigerator door plate

CN117887145BActive Publication Date: 2026-10-09HEFEI MIDEA REFRIGERATOR CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211229816.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-09
Publication Date
2026-10-09
Estimated Expiration
2042-10-09

AI Technical Summary

Technical Problem

[0005]但是,二氧化硅气凝胶加入PVC基体中,两者结合力欠佳,从而对PVC的整体性能和外观有一定影响

Benefits of technology

[0019]This invention provides a silica aerogel modified with a specific coupling agent, wherein the coupling agent has the chemical formula R-COCl, R-COOH, or R-NCO, where R is a chloroalkyl group with a carbon chain length between 4 and 12. Based on this, the active functional group in the coupling agent reacts with the silanol groups on the surface of the silica aerogel, linking C4-C12 chloroalkyl groups to the aerogel surface. When the aerogel is added to a PVC matrix, the C4-C12 chloroalkyl groups interact with the PVC matrix, improving the bonding force between the silica aerogel and the PVC matrix, thereby ensuring the overall performance of the PVC.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003881207680000101
    Figure BDA0003881207680000101
  • Figure BDA0003881207680000111
    Figure BDA0003881207680000111
  • Figure HDA0003881207690000011
    Figure HDA0003881207690000011
Patent Text Reader

Abstract

The application relates to the field of materials and provides a modified silica aerogel, a polyvinyl chloride composition, a modified polyvinyl chloride plate and a refrigerator door plate. The modified silica aerogel is a silica aerogel modified by a coupling agent, the chemical formula of the coupling agent is R-COCl, R-COOH or R-NCO, wherein R is a chloroalkyl with a carbon chain length of 4-12. The silica aerogel modified by the specific coupling agent is reacted with the silicon hydroxyl on the surface of the silica aerogel through the active functional groups in the coupling agent, and the chloroalkyl with a length of C4-C12 is linked to the surface of the aerogel. When the aerogel is added into a PVC matrix, the chloroalkyl with a length of C4-C12 reacts with the PVC matrix, the binding force between the silica aerogel and the PVC matrix is improved, and thus the performance of the whole PVC is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials, and more particularly to a modified silica aerogel, a polyvinyl chloride composition, a modified polyvinyl chloride sheet, and a refrigerator door panel. Background Technology

[0002] Polyvinyl chloride (PVC) is a polymer formed by the polymerization of vinyl chloride monomer (VCM) through a free radical polymerization mechanism under the initiation of peroxides, azo compounds, or under the influence of light and heat. PVC has a wide range of applications, including building materials, industrial products, daily necessities, flooring, floor tiles, artificial leather, pipes, wires and cables, packaging films, bottles, foaming materials, sealing materials, and fibers. However, due to its poor thermal stability, PVC generally requires the addition of fillers to improve its performance.

[0003] Traditional reinforced PVC mainly improves the strength of the PVC matrix by using inorganic fillers such as calcium carbonate and talc. However, this traditional method increases the weight of the PVC sheet, and the large amount of inorganic particles filler will form thermal conduction channels inside the matrix, reducing the thermal insulation performance of the PVC matrix. If used in refrigerator doors, it will not reduce the refrigerator's energy consumption.

[0004] Later, it was proposed to add silica aerogel to the PVC matrix. Aerogel particles have a hollow structure with a hard silica layer on the surface, resulting in high particle strength and a strong reinforcing effect on the plastic matrix. The hollow internal structure of the aerogel also leads to its low density. Using aerogel powder to fill the PVC matrix not only strengthens the matrix and increases the surface hardness of the PVC sheet, thus improving scratch resistance, but also introduces numerous voids within the PVC matrix, improving its thermal insulation properties while simultaneously reducing the density of the PVC sheet.

[0005] However, when silica aerogel is added to the PVC matrix, the bonding force between the two is poor, which has a certain impact on the overall performance and appearance of PVC. Summary of the Invention

[0006] The present invention aims to at least solve one of the technical problems existing in the related art. To this end, the present invention proposes a modified silica aerogel.

[0007] According to an embodiment of the present invention, the modified silica aerogel is a coupling agent-modified silica aerogel, wherein the chemical formula of the coupling agent is R-COCl, R-COOH or R-NCO, wherein R is a chloroalkyl group with a carbon chain length between 4 and 12.

[0008] According to some embodiments of the present invention, the coupling agent has the chemical formula R-NCO.

[0009] According to some embodiments of the present invention, R is a chloroalkyl group with a carbon chain length between 8 and 12.

[0010] Secondly, the present invention provides a method for preparing modified silica aerogel, comprising: mixing silica aerogel with a volatile aprotic organic solvent to obtain a suspension, mixing the suspension with the coupling agent, reacting for 2-6 hours, and then removing the solvent.

[0011] Thirdly, the present invention provides a polyvinyl chloride composition comprising polyvinyl chloride and the above-mentioned modified silica aerogel.

[0012] According to some embodiments of the present invention, the particle size of the modified silica aerogel is 1-5 micrometers.

[0013] According to some embodiments of the present invention, the modified silica aerogel has a mass percentage content of 10-15% in the polyvinyl chloride composition.

[0014] According to some embodiments of the present invention, the polyvinyl chloride composition comprises, by weight, the following components: 65-80 parts of polyvinyl chloride, 10-15 parts of modified silica aerogel, 10-15 parts of plasticizer, and 0-5 parts of calcium-zinc stabilizer.

[0015] Fourthly, the present invention provides a modified polyvinyl chloride sheet, the raw material of which includes the above-mentioned polyvinyl chloride composition.

[0016] Fifthly, the present invention also provides a method for preparing modified polyvinyl chloride sheets, comprising: blending the above-mentioned polyvinyl chloride composition by means of a twin-screw extruder and extruding it into sheets.

[0017] In a sixth aspect, the present invention also provides a refrigerator door panel, comprising the above-mentioned modified polyvinyl chloride sheet or the modified polyvinyl chloride sheet prepared by the above-mentioned preparation method.

[0018] The above-described one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects:

[0019] This invention provides a silica aerogel modified with a specific coupling agent, wherein the coupling agent has the chemical formula R-COCl, R-COOH, or R-NCO, where R is a chloroalkyl group with a carbon chain length between 4 and 12. Based on this, the active functional group in the coupling agent reacts with the silanol groups on the surface of the silica aerogel, linking C4-C12 chloroalkyl groups to the aerogel surface. When the aerogel is added to a PVC matrix, the C4-C12 chloroalkyl groups interact with the PVC matrix, improving the bonding force between the silica aerogel and the PVC matrix, thereby ensuring the overall performance of the PVC.

[0020] Furthermore, the polyvinyl chloride composition of the present invention is blended and extruded into sheets using a twin-screw extruder, forming a single-step process. This process is simple, with high production efficiency and yield. The resulting sheets have scratch resistance and thermal insulation properties, and can be used as refrigerator doors.

[0021] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the coupling agent being added to the PVC matrix in an embodiment of the present invention. Detailed Implementation

[0023] The embodiments of the present invention will be described in further detail below with reference to examples. These examples are for illustrative purposes only and should not be construed as limiting the scope of the invention.

[0024] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0025] According to an embodiment of the present invention, the modified silica aerogel is a coupling agent-modified silica aerogel, wherein the chemical formula of the coupling agent is R-COCl, R-COOH or R-NCO, wherein R is a chloroalkyl group with a carbon chain length between 4 and 12.

[0026] Traditional reinforced PVC mainly improves the strength of the PVC matrix by using inorganic fillers such as calcium carbonate and talc. However, this traditional method increases the weight of the PVC sheet, and the large amount of inorganic particles filler will form thermal conduction channels inside the matrix, reducing the thermal insulation performance of the PVC matrix. If used in refrigerator doors, it will not reduce the refrigerator's energy consumption.

[0027] The traditional way to improve the thermal insulation performance of PVC is through microfoaming. Microfoaming can reduce the density of PVC sheets, while the numerous air bubbles in the matrix provide insulation. However, the microfoaming process is complex and requires highly sophisticated equipment. Furthermore, the pore walls of microfoamed PVC sheets lack rigid support, making them extremely prone to deformation. This results in a relatively soft sheet, which is not suitable for refrigerator doors.

[0028] This invention uses silica aerogel to fill a PVC matrix. The silica aerogel has a hollow microsphere structure with a hard silica surface and a hollow interior. Its hard silica shell provides support to the PVC resin matrix, increasing the matrix's hardness and thus its scratch resistance. Simultaneously, the silica aerogel filling creates pores within the PVC matrix, which improve the substrate's thermal insulation performance and reduce its density.

[0029] Furthermore, the bonding strength and compatibility between silica aerogel and the PVC matrix are also crucial. Poor bonding strength and compatibility can lead to uneven dispersion of the silica aerogel, resulting in suboptimal filling performance. Current technologies typically use silane coupling agents to modify silica aerogel, grafting C=C and C=O double bonds onto its surface to enhance its surface activity and thus improve its compatibility with PVC. However, the effect of silane coupling agent modification on improving the compatibility between silica aerogel and PVC is generally limited and requires further improvement.

[0030] This invention has discovered that using specific coupling agents with the chemical formulas R-COCl, R-COOH, or R-NCO, where R is a chloroalkyl group with a carbon chain length between 4 and 12, to modify silica aerogels allows the active functional groups in the coupling agent to chemically bond with the silanol groups on the surface of the silica aerogel, linking the C4-C12 chloroalkyl groups to the aerogel surface. When the aerogel is added to a PVC matrix, the C4-C12 chloroalkyl groups interact with the PVC matrix, improving the bonding force between the silica aerogel and the PVC matrix, thereby ensuring the overall performance of the PVC. A schematic diagram of the coupling agent after being added to the PVC matrix is ​​shown below. Figure 1 As shown.

[0031] According to some embodiments of the present invention, the coupling agent has the chemical formula R-NCO. R-COCl has high reactivity; while binding to the silanol groups on the aerogel surface, it can also react with trace amounts of water in the reaction system, losing its activity and resulting in low binding efficiency. R-COOH exhibits weak esterification with the silanol groups on the aerogel surface, leading to a longer grafting reaction time and thus lower efficiency. Both R-COCl and RCOOH bind to the aerogel surface via ester bonds, which are prone to hydrolysis, resulting in a low grafting rate on the aerogel surface. In contrast, R-NCO exhibits better reactivity with silanol groups, enabling rapid grafting. Furthermore, the grafted carbamate bonds are relatively strong and resistant to hydrolysis, achieving the optimal surface modification effect.

[0032] According to some embodiments of the present invention, R is a chloroalkyl group with a carbon chain length between 8 and 12.

[0033] This invention reveals that the carbon chain length of the chloroalkyl group is crucial to the final bonding strength between the silica aerogel and the PVC matrix. If the carbon chain length is less than 4, the molecular chain grafted onto the aerogel surface is too short to effectively entangle with the matrix molecular chains, resulting in insufficient compatibility between the aerogel and the matrix. If the carbon chain length is too long (>12), the long carbon chain coils and wraps around the active groups at the ends, preventing the active groups from being exposed and grafting with the silanol groups on the aerogel, thus reducing grafting efficiency. A more preferred carbon chain length range is 8-12.

[0034] Secondly, the present invention provides a method for preparing modified silica aerogel, comprising: mixing silica aerogel with a volatile aprotic organic solvent to obtain a suspension, mixing the suspension with the coupling agent, reacting for 2-6 hours, and then removing the solvent.

[0035] Among them, volatile aprotic organic solvents can be dichloromethane, acetone, etc.

[0036] Solvent removal can be achieved using conventional methods in the field, such as vacuum removal.

[0037] Thirdly, the present invention provides a polyvinyl chloride composition comprising polyvinyl chloride and the above-mentioned modified silica aerogel.

[0038] In summary, the polyvinyl chloride composition containing the above-mentioned modified silica aerogel has better reinforcement than traditional inorganic filler reinforcement, better thermal insulation than traditional micro-foaming methods, and the modified silica aerogel has a strong bonding force with polyvinyl chloride, resulting in superior overall performance of the polyvinyl chloride composition.

[0039] According to some embodiments of the present invention, the particle size (D50) of the modified silica aerogel is 1-5 micrometers.

[0040] The particle size (D50) of the modified silica aerogel can be any value within the aforementioned range, such as 1 micrometer, 1.5 micrometers, 2 micrometers, 2.5 micrometers, 3 micrometers, 3.5 micrometers, 4 micrometers, 4.5 micrometers, or 5 micrometers. In existing technologies, silica aerogel particles with relatively large diameters, such as around 30 micrometers, are generally selected. However, this invention has found that controlling the particle size of the silica aerogel powder after specific modification to 1-5 micrometers yields better results. If the particle size is less than 1 micrometer, the aerogel pore diameter is too small, resulting in poor thermal insulation performance; if it is greater than 5 micrometers, protrusions will form on the surface, leading to poor appearance. Furthermore, large aerogel particles easily create stress concentration and defects within the board, increasing the board's brittleness. This is why using hollow glass beads to fill PVC is less effective than using the silica aerogel of this invention. Hollow glass microspheres have a minimum diameter of 10 μm. Using hollow glass microspheres can achieve low density, high hardness, and high thermal insulation; however, if the particle size is too large, the board becomes very brittle, and the material's elongation at break is low.

[0041] In this invention, the particle size of the modified silica aerogel is controlled to be 1-5 micrometers, which can be achieved by adjusting the reaction rate of aerogel formation, drying temperature and time, and the linear speed of grinding and dispersion.

[0042] According to some embodiments of the present invention, the modified silica aerogel has a mass percentage content of 10-15% in the polyvinyl chloride composition.

[0043] The cost of silica aerogel is significantly higher than that of PVC (PVC material price < 8 yuan / kg; aerogel price generally exceeds 20 yuan / kg). Modified silica aerogel is even more expensive. Therefore, it is necessary to minimize the mass percentage of modified silica aerogel in the PVC composition. In existing technologies, the addition amount of modified silica aerogel is generally 20-40%, mostly around 30%. This invention, due to the good compatibility of the modified silica aerogel and precise particle size control, only requires 10-15% addition. While ensuring mechanical and thermal insulation properties, this significantly reduces production costs and allows for widespread application.

[0044] According to some embodiments of the present invention, the polyvinyl chloride composition comprises, by weight, the following components: 65-80 parts of polyvinyl chloride, 10-15 parts of modified silica aerogel, 10-15 parts of plasticizer, and 0-5 parts of calcium-zinc stabilizer.

[0045] Further, by weight, the polyvinyl chloride composition comprises the following components: 70 parts polyvinyl chloride, 15 parts modified silica aerogel, 10 parts plasticizer, and 5 parts calcium-zinc stabilizer.

[0046] Plasticizers are widely used polymer additives in industrial production, also known as plasticizers. The use of plasticizers can improve the performance of polymer materials, reduce production costs, and increase production efficiency. Especially in polyvinyl chloride (PVC) plastic products, phthalate plasticizers are added to increase the plasticity and strength of the plastic. The main function of plasticizers is to weaken the secondary valence bonds between resin molecules, increase the mobility of resin molecular bonds, reduce the crystallinity of resin molecules, increase the plasticity of resin molecules, and enhance their flexibility and ease of processing. Therefore, plasticizers are generally indispensable in PVC compositions. PVC easily decomposes at high temperatures, releasing hydrogen chloride, leading to material degradation. To improve the stability of PVC materials during the molding process, a small amount of calcium-zinc stabilizers is also added to the plastic formulation.

[0047] In some embodiments of the present invention, the polyvinyl chloride composition is formulated as described above, which can yield a polyvinyl chloride material with good processing performance and a good balance of mechanical and thermal insulation properties.

[0048] Fourthly, the present invention provides a modified polyvinyl chloride sheet, the raw material of which includes the above-mentioned polyvinyl chloride composition.

[0049] As mentioned above, the above-mentioned polyvinyl chloride composition has good mechanical properties, thermal insulation properties, and processing properties. The boards prepared using raw materials including the above-mentioned polyvinyl chloride composition have high hardness, good scratch resistance, and good thermal insulation properties, which can be used to assist in thermal insulation and have a wide range of applications.

[0050] Fifthly, the present invention also provides a method for preparing modified polyvinyl chloride (PVC) sheets, comprising: blending the above-mentioned PVC composition using a twin-screw extruder and extruding it into sheets. The extrusion temperature is controlled at 140-180°C.

[0051] This invention uses a one-time molding process, which is simpler than making granules and then processing them into boards. It eliminates the need for multi-layer composites, thereby improving production efficiency and yield.

[0052] Furthermore, before the board is completely cooled, it can be passed through an embossing roller to form a corresponding texture on the board surface.

[0053] In a sixth aspect, the present invention also provides a refrigerator door panel, comprising the above-mentioned modified polyvinyl chloride sheet or the modified polyvinyl chloride sheet prepared by the above-mentioned preparation method.

[0054] The modified polyvinyl chloride sheet of this invention is used in refrigerator door panels, which have good scratch resistance and good heat insulation properties, which can also play an auxiliary role in heat preservation, reduce the thickness of the door and increase the usable space of the refrigerator.

[0055] The specific implementation method will be described below.

[0056] Example 1

[0057] This embodiment provides a polyvinyl chloride composition comprising 70 parts of polyvinyl chloride, 15 parts of modified silica aerogel, 12 parts of plasticizer (phthalate), and 3 parts of calcium-zinc stabilizer.

[0058] The modified silica aerogel is an R-NCO (R is a chloroalkyl group with a carbon chain length of 12) modified silica aerogel. Its preparation includes: placing the silica aerogel in dichloromethane to form a suspension, then adding the coupling agent R-NCO (R is a chloroalkyl group with a carbon chain length of 12) to the suspension, stirring the reaction for 6 hours, and then vacuum drying the solvent. After grinding and dispersion, the particle size D50 of the modified silica aerogel is controlled to be 2 micrometers.

[0059] This embodiment also provides a sheet material prepared from the above-mentioned polyvinyl chloride composition. The preparation method is as follows: modified silica aerogel is added to a twin-screw extruder via side feeding, mixed with polyvinyl chloride, plasticizer, and calcium-zinc stabilizer, and then extruded through a die to form a sheet material. The sheet material thickness is approximately 5 mm.

[0060] The obtained boards were subjected to the following performance tests: hardness was tested according to GB 6739—86 Coating Hardness Pencil Test Method; density was tested according to GB / T 1033 GB-T Determination of Density of Non-Foamed Plastics; thermal conductivity was tested according to ASTM-D5470 Steady-State Heat Flow Method; tensile strength was tested according to GB / T1040 Method.

[0061] As a result, the surface hardness of the plate in this embodiment can reach 6H, and the density can be controlled between 0.95-1.05 g / cm³. 3 The thermal conductivity is close to that of micro-foamed PVC (the thermal conductivity of pure PVC board is 0.028W / mK; the thermal conductivity of micro-foamed PVC is 0.010W / mK; the thermal conductivity of the sample is 0.011W / mK), and it has good thermal insulation performance. Its mechanical strength is close to that of PVC board.

[0062] Example 2

[0063] This embodiment provides a polyvinyl chloride composition comprising 75 parts polyvinyl chloride, 13 parts modified silica aerogel, 10 parts plasticizer (phthalate), and 2 parts calcium-zinc stabilizer.

[0064] The modified silica aerogel is an R-NCO (R is a chloroalkyl group with a carbon chain length of 4) modified silica aerogel. Its preparation includes: placing the silica aerogel in dichloromethane to form a suspension, then adding the coupling agent R-NCO (R is a chloroalkyl group with a carbon chain length of 4) to the suspension, stirring the reaction for 6 hours, and then vacuum drying the solvent. After grinding and dispersion, the particle size D50 of the modified silica aerogel is controlled to be 2 micrometers.

[0065] This embodiment also provides a sheet material prepared from the above-mentioned polyvinyl chloride composition. The preparation method is as follows: modified silica aerogel is added to a twin-screw extruder via side feeding, mixed with polyvinyl chloride, plasticizer, and calcium-zinc stabilizer, and then extruded through a die to form a sheet material. The sheet material thickness is approximately 5 mm.

[0066] Example 3

[0067] This embodiment provides a polyvinyl chloride composition comprising 70 parts of polyvinyl chloride, 15 parts of modified silica aerogel, 12 parts of plasticizer (phthalate), and 3 parts of calcium-zinc stabilizer.

[0068] The modified silica aerogel is an R-NCO (R is a chloroalkyl group with a carbon chain length of 8) modified silica aerogel. Its preparation includes: placing the silica aerogel in dichloromethane to form a suspension, then adding the coupling agent R-NCO (R is a chloroalkyl group with a carbon chain length of 8) to the suspension, stirring the reaction for 6 hours, and then vacuum drying the solvent. After grinding and dispersion, the particle size D50 of the modified silica aerogel is controlled to be 2 micrometers.

[0069] This embodiment also provides a sheet material prepared from the above-mentioned polyvinyl chloride composition. The preparation method is as follows: modified silica aerogel is added to a twin-screw extruder via side feeding, mixed with polyvinyl chloride, plasticizer, and calcium-zinc stabilizer, and then extruded through a die to form a sheet material. The sheet material thickness is approximately 5 mm.

[0070] Example 4

[0071] This embodiment provides a polyvinyl chloride composition comprising 70 parts of polyvinyl chloride, 15 parts of modified silica aerogel, 12 parts of plasticizer (phthalate), and 3 parts of calcium-zinc stabilizer.

[0072] The modified silica aerogel is an R-COCl (R is a chloroalkyl group with a carbon chain length of 12) modified silica aerogel. Its preparation includes: placing the silica aerogel in dichloromethane to form a suspension, then adding the coupling agent R-COCl (R is a chloroalkyl group with a carbon chain length of 12) to the suspension, stirring the reaction for 6 hours, and then vacuum drying the solvent. After grinding and dispersion, the particle size D50 of the modified silica aerogel is controlled to be 2 micrometers.

[0073] This embodiment also provides a sheet material prepared from the above-mentioned polyvinyl chloride composition. The preparation method is as follows: modified silica aerogel is added to a twin-screw extruder via side feeding, mixed with polyvinyl chloride, plasticizer, and calcium-zinc stabilizer, and then extruded through a die to form a sheet material. The sheet material thickness is approximately 5 mm.

[0074] Example 5

[0075] This embodiment provides a polyvinyl chloride composition comprising 70 parts of polyvinyl chloride, 15 parts of modified silica aerogel, 12 parts of plasticizer (phthalate), and 3 parts of calcium-zinc stabilizer.

[0076] The modified silica aerogel is an R-COOH (R is a chloroalkyl group with a carbon chain length of 12) modified silica aerogel. Its preparation includes: placing the silica aerogel in dichloromethane to form a suspension, then adding the coupling agent R-COOH (R is a chloroalkyl group with a carbon chain length of 12) to the suspension, stirring the reaction for 6 hours, and then vacuum drying the solvent. After grinding and dispersion, the particle size D50 of the modified silica aerogel is controlled to be 2 micrometers.

[0077] This embodiment also provides a sheet material prepared from the above-mentioned polyvinyl chloride composition. The preparation method is as follows: modified silica aerogel is added to a twin-screw extruder via side feeding, mixed with polyvinyl chloride, plasticizer, and calcium-zinc stabilizer, and then extruded through a die to form a sheet material. The sheet material thickness is approximately 5 mm.

[0078] Example 6

[0079] This embodiment provides a polyvinyl chloride composition comprising 70 parts of polyvinyl chloride, 15 parts of modified silica aerogel, 12 parts of plasticizer (phthalate), and 3 parts of calcium-zinc stabilizer.

[0080] The modified silica aerogel is an R-NCO (R is a chloroalkyl group with a carbon chain length of 12) modified silica aerogel. Its preparation includes: placing the silica aerogel in dichloromethane to form a suspension, then adding the coupling agent R-NCO (R is a chloroalkyl group with a carbon chain length of 12) to the suspension, stirring the reaction for 6 hours, and then vacuum drying the solvent. After grinding and dispersion, the particle size D50 of the modified silica aerogel is controlled to be 10 micrometers.

[0081] This embodiment also provides a sheet material prepared from the above-mentioned polyvinyl chloride composition. The preparation method is as follows: modified silica aerogel is added to a twin-screw extruder via side feeding, mixed with polyvinyl chloride, plasticizer, and calcium-zinc stabilizer, and then extruded through a die to form a sheet material. The sheet material thickness is approximately 5 mm.

[0082] Comparative Example 1

[0083] This comparative example provides a polyvinyl chloride composition that differs from Example 1 in that the modified silica aerogel is an R-NCO (R is a chloroalkyl group with a carbon chain length of 2) modified silica aerogel.

[0084] Comparative Example 2

[0085] This comparative example provides a polyvinyl chloride composition, which differs from Example 1 in that the modified silica aerogel is a silica aerogel modified with silane coupling agent KH550.

[0086] Comparative Example 3

[0087] This comparative example provides a polyvinyl chloride composition that differs from Example 1 in that the modified silica aerogel is replaced with an equal amount of unmodified silica aerogel.

[0088] The polyvinyl chloride (PVC) composition described above was used to prepare sheets using the same method as in Example 1. The resulting sheets achieved a surface hardness of 6H and a density that could be controlled between 0.95 and 1.05 g / cm³. 3 Its thermal conductivity is close to that of micro-foamed PVC, providing good insulation, but its mechanical strength is low, with a tensile strength of less than 10 MPa.

[0089] Comparative Example 4

[0090] This comparative example provides a polyvinyl chloride sheet, the raw material of which consists only of polyvinyl chloride and plasticizer.

[0091] The resulting sheet had a surface hardness of H and a density of 1.33 g / cm³. 3 It has high thermal conductivity, poor heat insulation performance, good mechanical strength, and tensile strength ≥15MPa.

[0092] Comparative Example 5

[0093] This comparative example provides a polyvinyl chloride sheet, the raw materials of which consist of polyvinyl chloride, calcium carbonate and plasticizer, and the amounts of each component are conventional in the art.

[0094] The resulting sheet material achieved a surface hardness of 6H with a filler content exceeding 40% and a density exceeding 1.5 g / cm³. 3 It also has a high thermal conductivity and poor mechanical properties.

[0095] Comparative Example 6

[0096] This comparative example provides a polyvinyl chloride microfoamed board, and the preparation process refers to conventional processes in this field.

[0097] The resulting sheet material had a surface hardness of only HB at most, and its density could be controlled at 1 g / cm³. 3 It has a low thermal conductivity, good heat preservation, extremely poor mechanical strength, and a tensile strength of around 5 MPa.

[0098] The performance of the boards obtained in the above embodiments and comparative examples was tested using the same methods as in Embodiment 1. The results are shown in the table below.

[0099] Table 1

[0100]

[0101]

[0102] The results above show that, compared to pure PVC sheets, sheets with added calcium carbonate filler have a higher thermal conductivity, poorer insulation, and higher density; micro-foamed sheets have extremely low surface hardness and insufficient scratch resistance; while sheets with added silica aerogel are superior to pure PVC in terms of surface hardness, density, and insulation performance. Furthermore, using modified silica aerogel can improve the mechanical properties of the material, with its tensile strength comparable to pure PVC. Among various modified silica aerogels, those modified with coupling agents R-COCl, R-COOH, or R-NCO, where R is a chloroalkyl group with a carbon chain length between 4 and 12, show the best results.

[0103] Finally, it should be noted that the above embodiments are only for illustrating the present invention and not for limiting the present invention. Although the present invention has been described in detail with reference to the embodiments, those skilled in the art should understand that various combinations, modifications, or equivalent substitutions of the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention and should be covered within the scope of the claims of the present invention.

Claims

1. A modified silica aerogel, characterized in that, The modified silica aerogel is a coupling agent-modified silica aerogel, wherein the chemical formula of the coupling agent is R-COCl, R-COOH or R-NCO, wherein R is a chloroalkyl group with a carbon chain length between 4 and 12; the particle size D50 of the modified silica aerogel is 1-5 micrometers.

2. The modified silica aerogel according to claim 1, characterized in that, The coupling agent has the chemical formula R-NCO.

3. The modified silica aerogel according to claim 2, characterized in that, R is a chloroalkyl group with a carbon chain length between 8 and 12.

4. The method for preparing the modified silica aerogel according to any one of claims 1-3, characterized in that, include: A suspension is obtained by mixing silica aerogel with a volatile aprotic organic solvent. The suspension is then mixed with the coupling agent, and the reaction is carried out for 2-6 hours before the solvent is removed.

5. A polyvinyl chloride composition, characterized in that, Including polyvinyl chloride and the modified silica aerogel according to any one of claims 1-3.

6. The polyvinyl chloride composition according to claim 5, characterized in that, The modified silica aerogel has a mass percentage of 10-15% in the polyvinyl chloride composition.

7. The polyvinyl chloride composition according to claim 6, characterized in that, The polyvinyl chloride composition comprises, by weight, the following components: 65-80 parts of polyvinyl chloride, 10-15 parts of modified silica aerogel, 10-15 parts of plasticizer, and 0-5 parts of calcium-zinc stabilizer.

8. A modified polyvinyl chloride sheet, characterized in that, The raw materials include the polyvinyl chloride composition according to any one of claims 5-7.

9. A method for preparing modified polyvinyl chloride (PVC) sheets, characterized in that, include: The polyvinyl chloride composition according to any one of claims 5-7 is blended and extruded into sheets using a twin-screw extruder.

10. A refrigerator door panel, characterized in that, This includes the modified polyvinyl chloride sheet as described in claim 8 or the modified polyvinyl chloride sheet prepared by the preparation method described in claim 9.

Citation Information

Patent Citations

  • Inorganic heat insulation and heat preservation material and preparation method thereof

    CN105621942A

  • Silica aerogel-polypropylene lightweight thermal insulation material and preparation method thereof

    CN112321948A